Performance probabilities and outcome effects in technical-tactical factors with bout phase changes of mixed martial arts - Miarka, B.; Brito, C. J.; Amtmann, J. (International Journal of Performance Analysis in Sport, 2017)
The purpose of this study was to realise an objectivity performance analysis based on technical-tactical actions in different MMA spatiotemporal phases (i.e. keeping distance, clinch and ground combat), and to estimate the extent to which technical-tactical actions in different combat phases could increase the probability of winning. The sample was composed of 1,752 rounds of 584 UFC bouts (Winning vs. Losing) from 67 events in 2013 and 2014. Technical-tactical actions during spatiotemporal changes (i.e. keeping distance, clinch and ground) were observed, according to frequency of attempted and landed strikes (separated in leg, body and head orientations), takedowns, chokes, locks and submissions. Wilcoxon was applied to compare outcomes, and a logistic regression analysis was used to confirm the effects of technical-tactical actions on the dichotomous performance (losing vs. winning), p = .05. The main results showed significant differences in all spatiotemporal changes, except for head and leg strike attempts while keeping the distance. The performance probability was 69.6% for outcomes, 64.5% for winning vs. 74.7% for losing. Furthermore, when verified the Wald`s criterion, it is possible to corroborate that Head Strikes Landed Keeping Distance, Offensive Passes and Takedowns Landed were the most significant variables, which contributed to probability of predicting winning bouts.